THE INFLUENCE OF VARIATION OF HYDROXYPROPYL METHYLCELLULOSE AND TWEEN 80 CONCENTRATIONS ON PHYSICAL CHARACTERISTICS AND PHYSICAL STABILITIES GEL OF WATER DRY EXTRACT OF TEMULAWAK - PAWESTRI, SEKAR AYU; SAIFULLAH SULAIMAN, TEUKU NANDA (International Journal of Current Pharmaceutical Research, 2019)
Objective: Water extract of temulawak (Curcuma xanthorrhizaRoxb.) contains curcumin, which known has antibacterial, antiinflammation, and antifungal activity so that it has potential used as wound healing. The purpose of this study was formulating gel of water extract of temulawak made by variation of hydroxypropyl methylcellulose (HPMC) and tween 80 concentrations and investigating the influence of formulations on physical characteristics and physical stabilities gel. Methods: Gel was made by variation of HPMC and tween 80 concentrations (3,00%: 1,00%; 5,00%: 1,00%; 3,00%: 2,00%; 5,00%; 2,00%). Gel preparations was evaluated the physical characeristics by organoleptic test, homogeneity test, pH, viscosity, spreadability, adhesiveness, and stability. The physical properties were analyzed by software Design Expert 9. Results: The results showed that HPMC has dominant influenced on viscosity, spreadability, and adhesiveness. HPMC and tween 80 have not influence on organoleptic, homogeneity, and pH of the gel. Optimum formula is HPMC 5,00% and tween 80 1,00%. Optimum formula is stable on organoleptic, homogeneity, pH, viscosity, and adhesiveness; however spreadability of gel is not stable during 3 mo storage. Conclusion: Variation of HPMC and tween 80 concentrations influenced viscosity, spreadability, and adhesiveness, while they were not influenced on organoleptic, homogeneity, and pH of gel. HPMC had dominant influenced on viscosity, spreadability, and adhesiveness gel.